2016
DOI: 10.1002/pros.23221
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Trans‐Differentiation in Prostate Cancer Cells

Abstract: Neuroendocrine (NE) differentiation in prostate cancer (PCa) is an aggressive phenotype associated with therapy resistance. The complete phenotype of these cells is poorly understood. Clinical classification is based predominantly on the expression of standard NE markers. We analyzed the phenotype of NE carcinoma of the prostate utilizing in vitro methods, in silico, and immunohistochemical analyses of human disease. Results LNCaP cells, subjected to a variety of stressors (0.1% (v/v) fetal bovine serum, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 44 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…Under standard growth conditions, the resistant cells underwent a marked change in morphology, characterized by increased elongated neuronal‐like appearance (Figure 3A). Similar phenotypic changes have been observed using preclinical models cultured in androgen deprivation conditions 17 . The LNCaP JNJR cells formed clusters regardless of cell confluence while the LNCaP DMSO cells tended to separate until forming a confluent monolayer.…”
Section: Resultssupporting
confidence: 77%
“…Under standard growth conditions, the resistant cells underwent a marked change in morphology, characterized by increased elongated neuronal‐like appearance (Figure 3A). Similar phenotypic changes have been observed using preclinical models cultured in androgen deprivation conditions 17 . The LNCaP JNJR cells formed clusters regardless of cell confluence while the LNCaP DMSO cells tended to separate until forming a confluent monolayer.…”
Section: Resultssupporting
confidence: 77%
“…SLC35D3, which showed a dramatic up-regulation also in NEPC PDXs from the independent dataset GSE59984 (data not shown), is specifically expressed in the substantia nigra, striatum, and olfactory bulb in mouse brain and it functions as an ER chaperone for dopamine receptor D1 trafficking to the plasma membrane [47]. Finally, it has been demonstrated that NEFM was diffusely expressed in prostate cancer cells undergoing neuronal trans-differentiation [48] and NOL4 was described as a biomarker for aggressiveness prostate cancer [49]. In our study, we derived a NEPC signature starting from primary prostate adenocarcinomas, as assessed by an experienced pathologist.…”
Section: Discussionmentioning
confidence: 93%
“…Several different AR + /PSA + prostate cancer cell lines can be reprogrammed to intermediary “metastable” states with cancer stem cell (CSC) properties (exemplified by NE differentiation markers, an invasive phenotype, and robust tumor-initiating potential) upon anti-androgen treatment [35, 36]. These states, however, are transient and can be reversed to AR + states by stopping the treatment.…”
Section: Role Of Tumor Plasticity In Neuroendocrine Trans-differentiamentioning
confidence: 99%